Dressing the Lumad Body: Indigenous Peoples and the Development Discourse in Mindanao - Quizon, Cherubim A. (Humanities Diliman: A Philippine Journal of Humanities, 2013)
Since the passage of the Indigenous Peoples Rights Act (IPRA) in 1997, the term indigenous peoples or IPs has become codified in Philippine Law. However, legal usage of the term indigenous cultural communities/indigenous peoples (ICCs/IPs) contrasts starkly with the ways that members of these communities refer to themselves. In Southern Mindanao, members of government (GO) and non-government organizations (NGO) employ lumad to refer to the people that they are committed to assist; so do artists and cultural workers who draw on highland Mindanao cultural traditions. But Bagobo, T’boli, Mandaya or B’laan peoples in Southern Mindanao rarely refer to themselves as lumad in everyday speech. Those who do refer to themselves as lumad regularly engage with NGOs or the government and may be observed dressed in denotative clothing, with traditional chiefly emblems playing a central part. The profound significance of names and visual symbols in native claims to power is relevant to the Mindanao case. This paper analyzes how textile practices of the Bagobo, along with comparative data from neighboring groups, pose special challenges to the conceptual category of a pan-Mindanao native. Elderly women, most knowledgeable in cloth lore and manufacture, rarely refer to themselves as lumad; yet women traditionally made ceremonial clothes for men, and continue to do so today. These clothes signal the men’s stature as dátu, and the means by which these textiles are acquired remain within the purview of women. How does the lumad/IP discourse depend on the erasure of group- and gender-specific knowledge systems? Using local delineations of a pan-Mindanao or pan-Philippine “indigenous person,” this paper will re-examine lumad as a political category and problematize its meaning as a cultural referent.
Keywords: Indigenous peoples, lumad, material culture, Mindanao, textiles, ethnicity, Bagobo